2021
DOI: 10.3390/f12040465
|View full text |Cite
|
Sign up to set email alerts
|

Genetic, Morphological, and Environmental Differentiation of an Arid-Adapted Oak with a Disjunct Distribution

Abstract: The patterns of genetic and morphological diversity of a widespread species can be influenced by environmental heterogeneity and the degree of connectivity across its geographic distribution. Here, we studied Quercus havardii Rydb., a uniquely adapted desert oak endemic to the Southwest region of the United States, using genetic, morphometric, and environmental datasets over various geographic scales to quantify differentiation and understand forces influencing population divergence. First, we quantified varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 94 publications
0
13
0
Order By: Relevance
“…Our microsatellite dataset had 2.6% missing data (Figure S5 ), and a total of 244 alleles were observed in situ and 186 alleles ex situ. Detailed genetic summary statistics for each in situ population can be found in Zumwalde et al ( 2021 ), who showed that patterns of differentiation from genetic, morphological, and environmental datasets primarily corresponded to the disjunction of populations from the eastern and western regions of the species’ geographic range. Additionally, Zumwalde et al ( 2021 ) noted that western populations generally had higher levels of genetic diversity and lower relatedness when compared to eastern populations.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our microsatellite dataset had 2.6% missing data (Figure S5 ), and a total of 244 alleles were observed in situ and 186 alleles ex situ. Detailed genetic summary statistics for each in situ population can be found in Zumwalde et al ( 2021 ), who showed that patterns of differentiation from genetic, morphological, and environmental datasets primarily corresponded to the disjunction of populations from the eastern and western regions of the species’ geographic range. Additionally, Zumwalde et al ( 2021 ) noted that western populations generally had higher levels of genetic diversity and lower relatedness when compared to eastern populations.…”
Section: Resultsmentioning
confidence: 99%
“…This lack of a clear signal for a single k suggests a hierarchical structure as might be expected for a widespread species. We, therefore, do not conclude there is a “best” value of k for this dataset, but we set k = 2 as it is biologically plausible (see also Zumwalde et al, 2021 ) and will allow comparison of the garden and regional in situ samples. This differentiation was also visible in a DAPC plot (Figure S7 ) suggesting that the genetic composition of garden populations is more similar to eastern populations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One study examines a uniquely adapted desert oak with a disjunct distribution using genetic, morphometric and environmental datasets. The authors present conservation and taxonomic implications of their findings [5]. A second paper examines the genetic diversity of three threatened oaks, comparing levels of diversity to that of common oaks and testing for correlations with range size, population size, and abiotic variations.…”
mentioning
confidence: 99%